5PSQ-109 Ransomware attack on a cytotoxic preparation unit (CPU): what now?. Issue 1 (23rd March 2023) - Lourenço, M; Canário, C; Costa, G; Duarte, H; Alcobia, A
Abstract : Background and Importance: The informatisation of processes has increased the susceptibility of the healthcare sector to computer attacks through ransomware. These can manifest by the impossibility of accessing the internet, and computer systems, with consequent interruption of electronic prescription, registration in patient diary, consultation of previous clinical data, request for means diagnostic tools, among others. Pharmaceutical Services are particularly vulnerable to these attacks. Aim and Objectives: The aim of this work was to systematise the strategies adopted during the cyberattack, minimising the error and allowing the work to be carry out at the CPU, with the elaboration of a guideline to be adopted in a future cyberattack. Material and Methods: Retrospective study between April 26 and May 10, 2022. Results: CPU was restructured in order to guarantee its functionality. Through the information on paper from the production maps of April 2022, chemotherapy protocols, charts with reconstitution/dilution of used drugs, literature and coordination of information with the nursing and medical team, it was possible prevent the collapse of the unit. It was performed a daily survey of patients marked in agenda, and respective information about the cycle. In the first 15 days of attack, 28.8% (n=132) of scheduled patients (n=458) were unchecked due to lack of access to complementary means of diagnosis and history of chemotherapy protocols. The preparation of cytotoxics was possible through the elaboration of manual labels (n=615), using the validation of paper prescriptions. In the first week (April 26 to 29) 41.9% (n=67) of the patients (n=160) were unchecked and in the second week (May 2 to 6) 25% (n=54) of patients (n=216). In the initial days of cyberattack no new patients were scheduled. Conclusion and Relevance: Faced with the reality of a computer attack, the CPU priority was to ensure a safety preparation of chemotherapy. On the other hand, this attack showed that it is crucial to have mechanisms of replacement of information such as the chemotherapy prescriptions file. Anticipating future cyberattacks, a guideline has been developed to ensure circuit safety in case of computer failure. References and/or Acknowledgements: 1. Not applicable. Conflict of Interest: No conflict of interest